POLA KOMUNIKASI ORGANISASI PASUBAYAN DESA ADAT DI BALI - Abdi Pakumara, Pande Ngurah Raditya; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
ABSTRAK   Pasubayan Desa Adat organization is an informal organization consisting of 39 Desa Adat in Bali. The organization of Pasubayan Desa Adat was formed on the basis of the purpose to preserve the environment and culture of Bali’s land. The purpose of this research is to explain communication pattern in Pasubayan Desa Adat organization. This research used descriptive qualitative research type. informants in this research are were chosen by using purposive technique and data obtained through interview to informant and documentation studies. Analytical techniques in this study using the stages of data reduction, data presentation, and withdrawal of conclusions. This study found that the organization of Pasubayan Desa Adat has a non-hierarchical organizational structure. Communication pattern in Pasubayan Desa Adat organization is a stellar or all-channel, which occurs during interaction of communication between members in social media (WhatsApp group and SMS) and at the time of formal and informal interaction that occurs directly between members.   Keywords: Communication Pattern , Organization, Pasubayan,